MATHEMATICAL MODEL OF AIRCRAFT TAKE-OFF IN COMPLEX METEOROLOGICAL CONDITIONS - Shishkov , O. F (Problems of Informatization and Management, 2021)
The developed mathematical model establishes a quantitative relationship between the reliability of the aerodrome light signal system and the level of flight safety at the stage of aircraft takeoff in difficult meteorological conditions and is proposed to be used as a basis for assessing and standardizing the reliability of the aerodrome light signal system.